Preparation of Porous Alumina through the Precipitation of Aluminium Hydroxide in the Presence of Surfactants - Nagi R.E. Radwan; Asem A. Atia; A.M. Youssef (Adsorption Science & Technology, 1999)
Different aluminas were prepared through the precipitation of aluminium hydroxide in the absence and presence of various surfactants, followed by calcination at different temperatures. Examples of anionic and cationic surfactants employed were sodium dioctylsulphosuccinate (AOT) and dodecylamine hydrochloride (DAH), respectively. The surface properties of the samples obtained were evaluated through measurements of their BET surface areas using nitrogen adsorption at 77 K and the adsorption of Methyl Orange from aqueous solution at 30°C. The addition of cationic surfactant during the precipitation process produced alumina with a high surface area, whereas only a limited change in the surface properties was induced by the anionic surfactant.